2019
DOI: 10.3390/nano9020164
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Application of Nanocellulose: From Industry to Skin Tissue Engineering and Wound Healing

Abstract: Nanocellulose is cellulose in the form of nanostructures, i.e., features not exceeding 100 nm at least in one dimension. These nanostructures include nanofibrils, found in bacterial cellulose; nanofibers, present particularly in electrospun matrices; and nanowhiskers, nanocrystals, nanorods, and nanoballs. These structures can be further assembled into bigger two-dimensional (2D) and three-dimensional (3D) nano-, micro-, and macro-structures, such as nanoplatelets, membranes, films, microparticles, and porous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
187
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 275 publications
(204 citation statements)
references
References 293 publications
(393 reference statements)
5
187
0
1
Order By: Relevance
“…There is also much research about the application of BNC in wound healing. Experiments made on mice in vivo , in which they were subjected to a study of skin healing on their back, showed that BNC dressings accelerated the wound healing process in comparison to ordinary dressings (gauze) . The confirmation that the BNC dressings accelerate wound healing is the higher number of newly created blood vessels, a higher level of collagen expression and a lower number of mast cells infiltrating the damaged site .…”
Section: Bacterial Nanocellulose In Wound Dressingmentioning
confidence: 99%
See 4 more Smart Citations
“…There is also much research about the application of BNC in wound healing. Experiments made on mice in vivo , in which they were subjected to a study of skin healing on their back, showed that BNC dressings accelerated the wound healing process in comparison to ordinary dressings (gauze) . The confirmation that the BNC dressings accelerate wound healing is the higher number of newly created blood vessels, a higher level of collagen expression and a lower number of mast cells infiltrating the damaged site .…”
Section: Bacterial Nanocellulose In Wound Dressingmentioning
confidence: 99%
“…A study on guinea pigs showed that BNC membranes accelerated the treatment of thick wounds. Wounds were created by surgical removal of the skin (2 × 4 cm) from the back . Modulation with BNC membranes affects the healing of skin wounds.…”
Section: Bacterial Nanocellulose In Wound Dressingmentioning
confidence: 99%
See 3 more Smart Citations